Development of Quizizz Application-Based Test to Measure Science Process Skills of High School Students on Biodiversity Materials - Dian Pangestuti; Dewi Febriyana; Isna Robiatul Adhawiyah; Rifqi Tiara Febriyanti; Setiyo Prajoko (Universitas Tidar, 2021)
This study aimed to develop a valid science process skills test both in terms of content and constructs. The selected biodiversity material is integrated into this test. The quizizz application is used so that this test can be accessed online. This study uses the Research and Development (R&D) 4-D model, namely define, design, develop, and disseminate. The final product of this development research is a science process-based test instrument to measure student skills that have been declared valid and feasible by experts in the form of 50 multiple-choice questions. This research trial was conducted on 40 high school students majoring in Mathematics and Natural Sciences. Quantitative data analysis was carried out based on the internal characteristics of the test, such as validity, reliability, level of difficulty, and discriminatory power. The results showed that the validity test contained 28 valid questions and 22 invalid questions. In the difficulty index, there are 33 easy questions, 16 easy questions and 0 difficult questions. There is also a distinguishing power of good criteria consisting of 12 questions, sufficient criteria for 20 questions, and flawed criteria for 18 questions. In the validity test with the material aspect, an average of 74% quite valid, the construction aspect on average 77% quite valid, and the language aspect are 91% quite valid. The students' science process skills are also classified as good, with 76.22 in the high category.